Evaluation of the Health and Environmental Impacts of Smoking on Individuals and Society in Sebha City - Fatima Al-Imam; Mona Alasagir; Tarek Belkasm (AlQalam Journal of Medical and Applied Sciences, 2025)
Smoking is one of the most important environmental pollutants that negatively impacts the health of smokers and non-smokers and the environment. This study aimed to evaluate the impact of smoking (cigarettes and hookah) on health and the environment in the city of Sabha. Blood samples were taken from 100 men (90 smokers and 10 non-smokers) aged 17-60 at the central reference laboratory in Sabha. The study included questionnaires and blood tests using a CBC machine. The results showed that the most commonly used type of cigarette was Marlboro, and the least was Retmen. The highest rate of cigarette smoking was recorded in the 28-38 age group, at 45.6%, and the highest rate of hookah smoking was recorded in the 17-27 age group at 44.4%. The analysis showed no significant differences in white blood cell and platelet counts between smokers and nonsmokers. All cigarette smokers suffered from health problems, such as poor physical fitness (60-67.5%), and oral health problems (70% of hookah smokers). The study also indicated that smoking negatively impacted nonsmokers, leading to increased blood pressure. It was found that smoking residues constitute 38% of the solid waste in the city of Sabha. The results indicated that the waste resulting from smoking: cigarette butts, are disposed of in the main landfill by incomplete burning, which leaves a long-term negative environmental impact on the soil, microorganisms, and groundwater in the future, especially since the plastic fibers in cigarette butts gradually decompose under the influence of environmental factors.